METHODOLOGY FOR DEVELOPING FLEXIBILITY IN MIDDLE SCHOOL GIRLS (GRADES 5–9) WITHIN THE FRAMEWORK OF DIFFERENTIATED PHYSICAL TRAINING (Scientific journal of the Fergana State University, 2025)
The article examines the impact of a differentiated approach to physical training on the development of flexibility in girls from grades 5–9. The experiment was conducted over three months and involved two groups: an experimental group and a control group. The aim of the study was to develop a methodology focused on improving flexibility while considering the individual characteristics of the students. The results demonstrated that the use of individualized exercises increases the effectiveness of training sessions, enhancing flexibility, posture, and overall physical development